2022
DOI: 10.1167/tvst.11.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Confocal Microscopy in Type 1 Diabetes Mellitus: A Six-Year Longitudinal Study

Abstract: Purpose The current study describes corneal nerve morphology using in vivo confocal microscopy (IVCM) in patients with type 1 diabetes (T1D) who were followed up for 6 years, and it examines the relationship between corneal parameters and metabolic control of glucose and peripheral neuropathy. Methods Sixty-two participants (37 with T1D and 25 control participants) were assessed in 2011 and 2017. Participants with bilateral cataract surgery or controls who developed dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Additionally, many observational studies conducted both on T1DM patients and on streptozotocin-induced diabetic C57Bl/6J mice reported a correlation between the glycemic control as expressed by levels of HbA1c and corneal nerve parameters, in particular, CNFD and CNFL but also CNBD and beading frequencies [ 36 , 53 , 80 , 81 , 82 , 83 , 84 ].…”
Section: How Glycemic Parameters Affect Corneal Nerve Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, many observational studies conducted both on T1DM patients and on streptozotocin-induced diabetic C57Bl/6J mice reported a correlation between the glycemic control as expressed by levels of HbA1c and corneal nerve parameters, in particular, CNFD and CNFL but also CNBD and beading frequencies [ 36 , 53 , 80 , 81 , 82 , 83 , 84 ].…”
Section: How Glycemic Parameters Affect Corneal Nerve Fibersmentioning
confidence: 99%
“…ImageJ, particularly with its plugin NeuronJ, currently represents one of the most frequently used methods to conduct a semi-automated analysis of the sub-basal nerve plexus, since it has been used in multiple studies to assess parameters such as IWL, CNFL, CNFD, CNBD, beading frequencies, and corneal nerve thickness [ 30 , 42 , 48 , 84 , 88 , 90 , 93 , 119 ]. It is a validated open-source image analysis platform developed by the National Institutes of Health (NIH; Bethesda, MD, USA), which includes NeuronJ, a semi-automated nerve-tracing plugin that intuitively draws a line over the center of a visible nerve fiber as the nerve is traced [ 121 , 122 , 123 ].…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…It is also known that identifying a corneal pathology at its earliest stages is important for preventing more noticeable deterioration of visual acuity and optimizing the long-term prognosis. Concretely, microscopic en-face images of the living human corneal layers have revolutionized the observation, diagnosis and treatment of numerous eye conditions [ 2 , 3 ]. In the UK in 2013, over 2 million people were living with sight loss that accounted for £28.1 million spent from the budget of the national health system (NHS) per year [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the link between CNFL and glucose variability observed by Zhao et al [1] , we have previously shown that continuous subcutaneous insulin infusion with lower glucose variability, as compared to basal bolus insulin, was associated with corneal nerve regeneration, despite a comparable HbA1c [29] . In a recent longitudinal study of patients with type 1 diabetes over 6.5 years, those with the highest HbA1c (68.1–86.7 mmol/mol) showed corneal nerve loss, while those in the optimally controlled tertile (HbA1c, 35.0–54.0 mmol/mol) showed corneal nerve regeneration [30] . Recently, however, we have shown progressive corneal nerve fiber degeneration despite an improvement in HbA1c and total cholesterol [31] .…”
mentioning
confidence: 95%
“…[29] In a recent longitudinal study of patients with type 1 diabetes over 6.5 years, those with the highest HbA1c (68.1-86.7 mmol/mol) showed corneal nerve loss, while those in the optimally controlled tertile (HbA1c, 35.0-54.0 mmol/mol) showed corneal nerve regeneration. [30] Recently, however, we have shown progressive corneal nerve fiber degeneration despite an improvement in HbA1c and total cholesterol. [31] Corneal nerve regeneration has been demonstrated after bariatric surgery in obese subjects with [32] and without [33] diabetes, and was independently associated with an improvement in triglycerides, but not HbA1c.…”
mentioning
confidence: 96%